Correction: Synthesis of γ-alumina (Al2O3) nanoparticles and their potential for use as an adsorbent in the removal of methylene blue dye from industrial wastewater. Issue 1 (8th October 2018) - Ali, Shafqat; Abbas, Yasir; Zuhra, Zareen; Butler, Ian S.
Abstract : Correction for 'Synthesis of γ-alumina (Al2 O3 ) nanoparticles and their potential for use as an adsorbent in the removal of methylene blue dye from industrial wastewater' by Shafqat Ali et al., Nanoscale Adv., 2018, DOI: ; 10.1039/c8na00014j .